Fabricating biodegradable calcium phosphate/calcium sulfate cement reinforced with cellulose: in vitro and in vivo studies. Issue 2 (28th November 2022) - Li, Xiao-Dan; Yan, Da-Wei; Ren, Hao-Hao; Zhang, Qi-Yi; Yan, Yong-Gang
Abstract : The study explores the osteogenic differentiation mechanism and immune response of biodegradable calcium phosphate/calcium sulfate cements reinforced with cellulose. Abstract : Osteoporosis is a growing public health concern worldwide. To avoid extra surgeries, developing biodegradable bone cement is critical for the treatment of osteoporosis. Herein, we designed calcium phosphate/calcium sulfate cement reinforced with sodium carboxymethyl cellulose (CMC/OPC). It presents an appropriate physicochemical performance for clinical handling. Meanwhile, CMC/OPC bone cement promotes osteogenic differentiation in vitro . Results of the immune response in vitro and in vivo confirmed that increasing the cellulose content triggered macrophage switching into the M2 phenotype and CMC/OPC exhibited significant anti-inflammation. Furthermore, in vitro and in vivo degradation demonstrated that cellulose tailors the degradation rate of composite bone cement, which achieved a linear degradation process and could degrade by more than 90% for 12 weeks. In summary, the composite bone cement CMC/OPC is a promising candidate for bone repair applications.